A Background Study of Social Awareness in Urdu Poetry - Azam, Qurat ul ain; Murad, Rukhshanda (sourcecoder, 2025)
Social awareness has an infinite association with Urdu literature. Exactly, no one discussed social awareness? What is it? What is the association between awareness and Urdu literature. What is convenient for Urdu literature and social awareness. Urdu literature and social awareness are imperfect without one another. Every poet who is owned by society has feelings about the dissimilar aspects of class, poverty, and traditions. They write what they feel and how they feel, what is right or wrong in society they takes stand against it through there writing and poetry. In this research article, I have tried to discuss what social awareness is? It’s a relationship with Urdu literature and its convention in Urdu poetry with special reference in Urdu poetry.